PENGARUH VARIASI DOSIS BIOHERBISIDA LARUTAN DAUN AKASIA (Acacia mangium Wild) TERHADAP TERHAMBATNYA PERTUMBUHAN GULMA WEDUSAN (Ageratum conyzoides L.) - Lailatun Ni’mah; Achyani Achyani; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
The aims of this reseach is 1) to determine whether there is the effect of variations in the dosage of acacia leaf solution in inhibiting the growth of wedusan weed, 2) to determine the correct dosage variation in inhibiting the growth off wedusan weed. This type of reseach is experimental, this study used a completely randomized block design (RAKL) with 4 treatments and 6 replications, to determine the effect of variations in the dosage of acacia leaf solution data analysis was performed using parametric test (normal data) and further test to determine which treatment inhibited the growth of wedusan weeds. The parameters observed in this study were wedusan weed height (cm), wedusan weed growth rate (cm), and wedusan weed dry weight (grams). The result showed that giving acacia leaf solution had a significant effect on inhibition of high growth, growth rate, and dry weight of wedusan weeds.